Short-distance part of the interaction of D mesons and nucleons - Krein, G. [UNESP]; Vizcarra, V. E. [UNESP] (My University, 2008)
The short-distance part of the low energy interaction of D-mesons and nucleons is investigated in the context of a quark model. The quark model is based on Coulomb gauge QCD. The model contains a confining Coulomb potential and a transverse hyperfine interaction consistent with a finite gluon propagator in the infrared. The basic mechanism for the short-distance interaction between the D-mesons and nucleons is quark interchange. Using Resonating Group Method techniques an effective potential for the interaction between nucleons and D mesons can be obtained and used in a Lippmann-Schwinger equation to obtain differential cross-sections and phase shifts.